Subsídios para projeto de estruturas de aço protendidas - Aimi, Tainara (2015)
In Brazil, the concrete is predominant in the field of structural engineering, but on the other hand, the steel is gaining more and more space and, with it, resulting in the prestressing structural elements, always thinking of improving applications and economics, as an example, the beams, which are one of the most important elements for the stability of structures. The big problem of the research focuses on the analysis and design of structural elements in prestressed steel, and we know of no rule that addresses the same, helping to minimize the deformations and reducing the size of the cross section. Knowing that it helps reducing environmental costs, improving sustainability in steel structures using the material in the most appropriate way, it is being applied for roofs, columns, beams, locks, bridges and walkways and, with that, creating contributions to include in standard steel structures recommendations for prestressed steel structures. Showing its wide importance of use for structures of buildings with large spans and limitations beam heights, the work was based on measuring and analyzing the structural elements of prestressed steel, creating four types of computer applications in spreadsheets based on bibliographic references, of different prestressed elements: Fink beam with inner and outer wires, purlins and trusses. After, the validity was verified with modeling of finite element and the analysis with prestressed and not prestressed elements in the SAP program, showing that it is possible to use this type of structures in buildings, bridges and roofs. It was also verified that there is reduced deformation and effort when there are prestressing elements, helping to decrease the size of the structure